PATHOLOGIC AND MOLECULAR SUBTYPES CHARACTERISTICS OF OUR BREAST CANCER PATIENTS IN KOSOVO - Haxhiu, Brunilda Profka; Kondov, Goran; Abdullahu, Luljeta; Kurshumliu, Fisnik; Kondov, Borislav (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
To classify breast cancer cases by molecular subtypes (Luminal A, Luminal B [HER2-positive], Luminal B [HER2-negative], HER2-positive, and triple-negative). The secondary objective was to analyze associations between immunohistochemical markers, molecular subtypes, and established prognostic factors (stage, grade, age, and tumor location).  This prospective study included 100 patients diagnosed with breast cancer and treated at an oncology clinic. All patients underwent various treatment modalities, including surgical intervention. Radical mastectomy (RM) remained the predominant surgical approach, performed in 83% of cases, compared to 16% who underwent breast-conserving surgery (BCS). Across all molecular subtypes, RM combined with lymph node dissection was the primary surgical treatment. Even among patients with the Luminal A subtype, the ratio of BCS to RM was 1:3. Molecular subtypes were found to correlate with tumor volume and disease stage, reflecting differences in disease progression. A considerable number of cases were diagnosed at locally advanced stages, contributing to the preference for mastectomy over BCS. This tendency may reflect the need for more aggressive treatment strategies at the time of diagnosis due to the advanced nature of the disease. Keywords: breast cancer, molecular subtypes.